2014
DOI: 10.1016/j.otsr.2014.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Vascular injuries during closing-wedge high tibial osteotomy: A cadaveric angiographic study

Abstract: Descriptive cadaver study. Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…Neurovascular bundles were located close to the posterior tibial cortex. 10,19 The distance from the posterior tibial cortex to the neurovascular bundles was 9.4 ± 3.6 mm at 30 of flexion at 2.0 cm below the knee joint line. 19 In our study, the surgical procedures performed around the osteotomy site during OWHTO might have stimulated the stretched neurovascular bundles, even though they were protected by a Hohmann retractor.…”
Section: Discussionmentioning
confidence: 94%
“…Neurovascular bundles were located close to the posterior tibial cortex. 10,19 The distance from the posterior tibial cortex to the neurovascular bundles was 9.4 ± 3.6 mm at 30 of flexion at 2.0 cm below the knee joint line. 19 In our study, the surgical procedures performed around the osteotomy site during OWHTO might have stimulated the stretched neurovascular bundles, even though they were protected by a Hohmann retractor.…”
Section: Discussionmentioning
confidence: 94%
“…In a recent cadaver study, Darnis et al reported a mean distance of 10.6 mm between the saw blade and the popliteal artery in 90° of knee flexion. The authors recommend osteotomies in 90° of knee flexion, which is clinically unfeasible [5].…”
Section: Arterial Injuriesmentioning
confidence: 99%
“…Çalışma sonucunda vasküler yapıları korumak için tibiaya direkt temas eden bir koruyucu alet konulmasını önermişler. [70]…”
Section: Vasküler Yaralanmaunclassified